Coating reflecting film containing white light quantum dot coated organic particles and preparation method thereof
By using white-light quantum dots to coat organic particles, the problem of poor brightness loss and anti-adsorption effect of reflective film in large-sized displays is solved, and good anti-adsorption and light gain effects are achieved, preventing scratches of the light guide plate and improving The brightness of the monitor.
Patent Information
- Application Number
- CN202411745248.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing reflective films are problematic of loss of brightness and poor anti-adsorption effect caused by coated particles in large-sized displays, especially when using inorganic quantum dot materials, which are prone to scratch the light guide plate and lack self-luminous characteristics.
White light quantum dots are used to coat organic particles as coated particles. The quantum dots are firmly coated on the surface of organic particles through surface ligand exchange, and are evenly dispersed in the coating to form a raised structure to buffer external extrusion and form air barriers. The layer uses white quantum dots to generate white fluorescence to increase luminance under the excitation of the backlight source.
It improves the anti-adsorption effect and brightness of the reflective film, prevents scratches on the light guide plate, and provides light gain in the full visible light band, improving the overall brightness performance of the display.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical reflective films, and in particular to a coating reflective film containing white light quantum dots coated with organic particles and a preparation method thereof. Background Art
[0002] The reflective film is an important component in the display backlight module. Its main function is to reflect the light emitted downward from the light source back to the upper part of the backlight module for light compensation. Therefore, its ability to reflect light plays a decisive role in the overall brightness of the display. As displays gradually develop towards larger sizes, consumers' requirements for the brightness of displays are also increasing. The assembly of large-size displays is usually accompanied by the adsorption problem of the underlying reflective film and the light guide plate. The current common solution is to coat particles on the surface of the reflective film to form an air barrier layer between the reflective sheet and the light guide plate to avoid adsorption. However, coating is bound to cause a loss in the brightness of the reflective sheet, resulting in poor performance in large-size displays. Therefore, improving the brightness of the coated reflective sheet has become an important topic in the field of large-size displays.
[0003] The patent with publication number CN114637061A discloses a high-toughness and high-brightness reflective film and its preparation method. Its core technology is to achieve the purpose of improving brightness by coating a glue layer containing quantum dot material on the surface of the reflective film and generating optical gain through the quantum confinement effect of the quantum dot material itself.
[0004] However, the quantum dot materials used in this patent are inorganic particles such as silicon dioxide, titanium dioxide, ferroferric oxide or copper oxide. On the one hand, since these materials are rigid particles, they can easily scratch the softer light guide plate during assembly. Moreover, since the size of the material itself is nanometer-level, it is difficult to form an air barrier layer between the reflective film and the light guide plate, so the anti-adsorption effect is not ideal. On the other hand, since these particles themselves do not have the characteristics of self-luminescence, the brightness enhancement effect on the coated reflective film is not significant. Summary of the invention
[0005] The present invention aims to overcome the problem of brightness loss of the reflective film itself caused by coating particles on the surface of the reflective film in the prior art, and provides a coated reflective film containing organic particles coated with white light quantum dots and a preparation method. In the coating, organic particles coated with white light quantum dots are used as coating particles. Since the coating contains organic flexible particles, the coated reflective film provided by the present invention has a good anti-adsorption effect; in addition, since the surface of the coated particles is coated with white light quantum dots, the material can spontaneously generate white light emission under the excitation of a backlight source, which greatly increases the brightness of the coated reflective film.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A coated reflective film containing white light quantum dot-coated organic particles, comprising a white reflective base film and a coating coated on the surface of the white reflective base film; the raw materials in the coating include white light quantum dot-coated organic particles, an adhesive and an additive; In the white light quantum dot-coated organic particles, the white light quantum dots are ZnCuGaInS / ZnS quantum dots after surface ligand exchange with molecules containing thiol functional groups, the organic particles are one or more of PMMA particles, PBMA particles, PET particles, and PA particles, and the particle size of the organic particles is 3~50μm.
[0007] The present invention adds white light quantum dot-coated organic particles as coating particles in the coating of the reflective film; organic particles with larger particle sizes can form protrusions in the coating, and the material of the organic particles is relatively soft, so they can play a certain buffering role in the process of the backlight module being subjected to external extrusion, thereby preventing the bottom reflective sheet from scratching the light guide plate and causing white spots to be displayed; in addition, these protruding coating particles have a supporting role, thereby ensuring that an air barrier layer can be formed between the bottom reflective film and the upper light guide plate, thereby avoiding the light guide plate from directly contacting the adhesive coating to produce adhesion and causing dark shadows to be displayed.
[0008] At the same time, the present invention coats white light quantum dots on the surface of organic particles, and the ZnCuGaInS / ZnS quantum dots can emit white fluorescence in the entire visible light band. When the coated reflective film provided by the present invention is applied to the backlight module, the white light quantum dots on the surface of the coated particles will produce white light emission under the excitation of the backlight source, which is equivalent to introducing a second light source into the backlight, thereby increasing the amount of light returned from the bottom reflective film to the upper light guide plate, thereby achieving the effect of improving the brightness of the coated reflective film. Since the ZnCuGaInS / ZnS quantum dots produce fluorescence emission in the entire visible light band, the coated reflective film provided by the present invention has light gain in the blue, green and red light bands, and has a good effect on improving the brightness.
[0009] The present invention replaces the original oleic acid and oleylamine ligands on the surface of white light quantum dots with molecules containing thiol functional groups through surface ligand exchange. Since the thiol functional group has a greater electronegativity, it can form a stronger coordination bond with the surface of the quantum dots; at the same time, the thiol functional group generates thiol free radicals under the action of photoinitiator and UV, and these thiol free radicals can complete cross-linking with the unsaturated bonds in the organic particle molecules through click reactions, ensuring that the white light quantum dots can be firmly coated on the surface of the organic coated particles. Compared with the solution of directly mechanically mixing the white light quantum dots with the organic coated particles, the solution provided by the present invention can ensure that the white light quantum dots are uniformly dispersed in the coating liquid along with the organic coated particles, avoiding the white light quantum dots from being dispersed alone in the coating liquid to produce agglomeration or sedimentation. At the same time, the organic coated particles coated with the white light quantum dots are embedded in the adhesive coating, and the adhesive coating can also be used as a water and oxygen barrier layer to protect the quantum dots, thereby improving the luminescence stability of the white light quantum dots.
[0010] Preferably, in the white light quantum dot-coated organic particles, the mass ratio of white light quantum dots to organic particles is 1:14-25. If the white light quantum dots coated on the surface of the organic coated particles are too few, the amount of light compensation provided by the white light quantum dots after being excited is insufficient, resulting in an unsatisfactory brightness enhancement effect of the coated reflective film; conversely, due to the self-absorption phenomenon of white light quantum dots, if the quantum dots distributed on the surface of the organic coated particles are too dense, the fluorescence generated by a part of the quantum dots after being excited will be absorbed by another part of the quantum dots, which also affects the brightness enhancement effect of the coated reflective film.
[0011] Preferably, the molecule containing a thiol functional group is pentaerythritol tetrathioglycolate and / or γ-mercaptopropyltrimethoxysilane; during surface ligand exchange, the mass ratio of ZnCuGaInS / ZnS quantum dots to the molecule containing a thiol functional group is 1:30-50.
[0012] Preferably, the raw materials in the coating include, by weight: 3-8 parts of white light quantum dot-coated organic particles, 75-85 parts of adhesive, and 8-12 parts of auxiliary agent; the refractive index of the adhesive is 1.43-1.53. The adhesive with a refractive index within this range has good photoaffinity and will not affect the luminescent properties of the quantum dots.
[0013] Preferably, the adhesive is one of thermosetting acrylic glue, polyurethane resin, epoxy resin, and polyvinyl acetal resin; and the auxiliary agent is at least one of a dispersant, a curing agent, and an antistatic agent.
[0014] Preferably, in the coating, the coating amount of the white light quantum dots coated organic particles is 1.5-2.5 g / m 2 .
[0015] Preferably, the reflectivity of the white reflective base film is greater than 95%; the white reflective base film is one of a foamed polyethylene terephthalate base film, a polypropylene base film, and a polycarbonate base film.
[0016] Preferably, the thickness of the white reflective base film is 100-188 μm.
[0017] The present invention also provides a method for preparing the above-mentioned coating reflective film containing white light quantum dot-coated organic particles, comprising the following steps: (1) Preparation of ZnCuGaInS / ZnS quantum dot dispersion; (2) Quantum dot surface ligand exchange: ZnCuGaInS / ZnS quantum dot dispersion and a molecular solution containing thiol functional groups are mixed, and after stirring for reaction, a white light quantum dot dispersion after surface ligand exchange is obtained; (3) Coating organic particles: adding the white light quantum dot dispersion after surface ligand exchange to the organic particle dispersion, and adding a photoinitiator, stirring and reacting under ultraviolet irradiation and drying to obtain a white light quantum dot coated organic particle dispersion; (4) Preparation of coating liquid: adding the raw materials in the coating into the organic solvent and mixing them evenly to form the coating liquid; (5) Coating: coating the coating liquid on the surface of the white reflective base film, and obtaining the coated reflective film containing the white light quantum dot-encapsulated organic particles after curing.
[0018] Preferably, in step (2), the reaction is stirred under a protective atmosphere, the rotation speed during the stirring reaction is 800-1500 rpm, and the reaction time is 4-5 h.
[0019] Preferably, the photoinitiator in step (3) is dimethylphenylphosphine or TPO; step (3) is carried out at 180-200 W / m 2 The mixture was irradiated with ultraviolet light and stirred at 400-600 rpm for 2-3 hours.
[0020] Preferably, the organic solvent in the coating solution of step (4) is a mixed solvent of ethyl acetate and butyl acetate in a volume ratio of 1:0.5-2.
[0021] Preferably, in the coating solution of step (4), the mass ratio of the adhesive to the organic solvent is 1:2-3.
[0022] Preferably, the curing temperature in step (5) is 90-120° C., and the curing time is 2-4 min.
[0023] Therefore, the present invention has the following beneficial effects: (1) Adding white light quantum dot-coated organic particles as coating particles in the coating; the organic particles are larger in size and softer in material, which can prevent the bottom reflective sheet from scratching the light guide plate and causing white spots on the display; and can ensure that an air barrier layer can be formed between the bottom reflective film and the upper light guide plate, thus preventing the light guide plate from directly contacting the adhesive coating and causing adhesion and causing dark shadows on the display; (2) The white light quantum dots coated on the surface of the organic particles can emit white fluorescence in the entire visible light band. When excited by the backlight source, white light emission will be generated, which is equivalent to introducing a second light source into the backlight, thereby increasing the amount of light returned from the bottom reflective film to the upper light guide plate, thereby achieving the effect of improving the brightness of the coated reflective film; (3) Through surface ligand exchange, the original oleic acid and oleylamine ligands on the surface of white light quantum dots are replaced by molecules containing thiol functional groups. The thiol functional groups generate thiol free radicals under the action of photoinitiator and UV. These thiol free radicals can cross-link with the unsaturated bonds in the organic particle molecules through click reactions, ensuring that the white light quantum dots can be firmly coated on the surface of the organic coated particles. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific implementation methods.
[0025] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0026] Overall embodiment: A coated reflective film containing white light quantum dot-coated organic particles, comprising a white reflective base film and a coating coated on the surface of the white reflective base film; the raw materials in the coating include white light quantum dot-coated organic particles, an adhesive and an additive; In the white light quantum dot-coated organic particles, the white light quantum dots are ZnCuGaInS / ZnS quantum dots after surface ligand exchange with molecules containing thiol functional groups, the organic particles are one or more of PMMA particles, PBMA particles, PET particles, and PA particles, and the particle size of the organic particles is 3~50μm.
[0027] As a specific implementation manner, in the white light quantum dot-coated organic particles, the mass ratio of the white light quantum dots to the organic particles is 1:14-25.
[0028] As a specific implementation, the molecule containing a thiol functional group is pentaerythritol tetrathioglycolate and / or γ-mercaptopropyltrimethoxysilane; during surface ligand exchange, the mass ratio of ZnCuGaInS / ZnS quantum dots to the molecule containing a thiol functional group is 1:30~50.
[0029] As a specific implementation manner, the raw materials in the coating include, by weight: 3 to 8 parts of white light quantum dot-coated organic particles, 75 to 85 parts of adhesive, and 8 to 12 parts of auxiliary agents; the refractive index of the adhesive is 1.43 to 1.53.
[0030] As a specific implementation, the adhesive is one of thermosetting acrylic glue, polyurethane resin, epoxy resin, and polyvinyl acetal resin; the auxiliary agent is at least one of a dispersant, a curing agent, and an antistatic agent.
[0031] As a specific embodiment, in the coating, the coating amount of the white light quantum dots coated organic particles is 1.5-2.5 g / m 2 .
[0032] As a specific implementation manner, the reflectivity of the white reflective base film is greater than 95%; the white reflective base film is one of a foamed polyethylene terephthalate base film, a polypropylene base film, and a polycarbonate base film.
[0033] As a specific implementation, the thickness of the white reflective base film is 100-188 μm.
[0034] The method for preparing the above-mentioned coating reflective film containing white light quantum dot-coated organic particles comprises the following steps: (1) Preparation of ZnCuGaInS / ZnS quantum dot dispersion; (2) Quantum dot surface ligand exchange: ZnCuGaInS / ZnS quantum dot dispersion and a molecular solution containing thiol functional groups are mixed, and after stirring for reaction, a white light quantum dot dispersion after surface ligand exchange is obtained; (3) Coating organic particles: adding the white light quantum dot dispersion after surface ligand exchange to the dispersion of organic particles, and adding a photoinitiator, stirring and reacting under ultraviolet irradiation and drying to obtain white light quantum dot coated organic particles; (4) Preparation of coating liquid: adding the raw materials in the coating into the organic solvent and mixing them evenly to form the coating liquid; (5) Coating: coating the coating liquid on the surface of the white reflective base film, and obtaining the coated reflective film containing the white light quantum dot-encapsulated organic particles after curing.
[0035] As a specific implementation, in step (1), a ZnCuGaInS / ZnS quantum dot dispersion is prepared by referring to the method in patent CN117285930A.
[0036] As a specific implementation method, in step (2), the reaction is stirred under a protective atmosphere, the rotation speed during the stirring reaction is 800-1500 rpm, and the reaction time is 4-5 hours.
[0037] As a specific embodiment, the photoinitiator in step (3) is dimethylphenylphosphine or TPO; step (3) is performed at 180-200 W / m 2 The mixture was irradiated with ultraviolet light and stirred at 400-600 rpm for 2-3 hours.
[0038] As a specific implementation, the organic solvent in the coating solution of step (4) is a mixed solvent of ethyl acetate and butyl acetate in a volume ratio of 1:0.5-2.
[0039] As a specific implementation, in the coating solution of step (4), the mass ratio of the adhesive to the organic solvent is 1:2-3.
[0040] As a specific implementation, the curing temperature in step (5) is 90-120° C., and the curing time is 2-4 min.
[0041] Embodiment 1: A coated reflective film containing white light quantum dot-coated organic particles, comprising a white reflective base film with a thickness of 150 μm (Ningbo Changyang Technology Co., Ltd., reflective film FDX150, reflectivity 96.8%) and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating include 6.3 parts of white light quantum dot-coated organic particles, 82 parts of thermosetting acrylic glue with a refractive index of 1.48, 8 parts of a curing agent, 0.7 parts of an antistatic agent and 3 parts of a dispersant BYK-156.
[0042] The method for preparing the above-mentioned coating reflective film containing white light quantum dot-coated organic particles comprises the following steps: (1) Preparation of ZnCuGaInS / ZnS quantum dot dispersion: a) Dissolving zinc acetate in octadecene and n-dodecyl mercaptan in a volume ratio of 1:1 at 150° C. with stirring as a No. 1 zinc precursor solution, wherein the concentration of the precursor solution is 0.5 mol / L; b) dissolving zinc carbonate in a mixed solution of octadecene, n-dodecyl mercaptan and oleic acid in a volume ratio of 1:1:2 at 170° C. with stirring to obtain a No. 2 zinc precursor solution, wherein the concentration of the precursor solution is 0.5 mol / L; c) Weigh a certain amount of zinc stearate and dissolve it in octadecene and n-dodecyl mercaptan in a volume ratio of 1:2 at 200°C with stirring as a No. 3 zinc precursor solution. The concentration of the precursor solution is 0.5 mol / L; d) Add zinc iodide, cuprous iodide, gallium iodide, elemental sulfur, indium iodide in a molar ratio of 1:0.04:0.3:0.6:0.03 and oleylamine and n-dodecyl mercaptan in a volume ratio of 1:0.5 into a three-necked flask, react at 240° C. under a N2 environment for 20 min, then inject the No. 1 zinc precursor solution in step a) into the three-necked flask with a syringe to react for 60 min, and the volume ratio of the precursor solution injected to the mixed solution in the flask is 1:2; e) injecting the zinc precursor solution No. 2 in step b) in the same amount as that in step d) into the reaction flask in step d), and reacting at a constant temperature of 240° C. for 60 min; f) injecting the zinc precursor solution No. 3 in step c) in an amount equal to that in step d) into the reaction flask in step e), and reacting at 240° C. for 60 min. After the reaction is completed, cooling the temperature in an ice bath to room temperature to obtain a ZnCuGaInS / ZnS quantum dot stock solution; g) adding ethyl acetate in a volume ratio of 1:2 to the ZnCuGaInS / ZnS quantum dot stock solution obtained in step f) and centrifuging at high speed to remove the solvent in the stock solution, then dispersing the precipitate obtained by centrifugation in toluene and centrifuging at high speed for a second time to remove nanocrystals with larger particle sizes, retaining the supernatant, and obtaining a ZnCuGaInS / ZnS dispersion; (2) Quantum dot surface ligand exchange: dissolve pentaerythritol tetrathioglycolate in toluene to obtain a pentaerythritol tetrathioglycolate solution; mix the ZnCuGaInS / ZnS quantum dot dispersion and the pentaerythritol tetrathioglycolate solution at a mass ratio of ZnCuGaInS / ZnS quantum dots to pentaerythritol tetrathioglycolate of 1:35, stir at 1000 rpm for 4 h under nitrogen protection to obtain a white light quantum dot dispersion after surface ligand exchange; (3) Encapsulation of organic particles: PMMA particles with a particle size of 7 μm were dispersed in a toluene solution, and a dispersant BYK-156 was added to assist in dispersion, and then a white light quantum dot dispersion and a photoinitiator TPO after surface ligand exchange were added. The mass ratio of the added white light quantum dots to the PMMA particles was 1:15, and the mass of the added photoinitiator was 2% of the total mass of the PMMA particles and the white light quantum dots. The reaction mixture was heated to 190 W / m 2 After UV irradiation and stirring at 500 rpm for 2 h, the mixture was dried to obtain organic particles coated with white light quantum dots; (4) preparing a coating liquid: firstly, ethyl acetate and butyl acetate are mixed in a volume ratio of 1:1 to prepare an organic mixed solvent, and then thermosetting acrylic glue, white light quantum dot-coated organic particles and a curing agent, an antistatic agent and a dispersant are dissolved in the organic mixed solvent in proportion, and mixed evenly to prepare a coating liquid; the mass ratio of thermosetting acrylic glue to the organic mixed solvent in the coating liquid is 1:2; (5) Coating: Use an OSP-20 wire rod to coat the coating liquid on the surface of the white reflective base film. The coating amount of the white light quantum dot-coated organic particles is 1.8 g / m 2 After curing at 100° C. for 3 minutes, the coated reflective film containing white light quantum dot-coated organic particles is obtained.
[0043] Embodiment 2: A coated reflective film containing white light quantum dot-coated organic particles, comprising a white reflective base film (Ningbo Changyang Technology Co., Ltd., reflective film FDX150) with a thickness of 150 μm and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating include 6.5 parts of white light quantum dot-coated organic particles, 82 parts of thermosetting acrylic glue with a refractive index of 1.48 and 8 parts of a curing agent, 0.7 parts of an antistatic agent and 2.8 parts of a dispersant BYK-156.
[0044] The method for preparing the above-mentioned coating reflective film containing white light quantum dot-coated organic particles comprises the following steps: (1) Preparation of ZnCuGaInS / ZnS quantum dot dispersion: the method is the same as that in Example 1; (2) Quantum dot surface ligand exchange: dissolve pentaerythritol tetrathioglycolate in toluene to obtain a pentaerythritol tetrathioglycolate solution; mix the ZnCuGaInS / ZnS quantum dot dispersion and the pentaerythritol tetrathioglycolate solution at a mass ratio of ZnCuGaInS / ZnS quantum dots to pentaerythritol tetrathioglycolate of 1:36, stir at 800 rpm for 5 h under nitrogen protection to obtain a white light quantum dot dispersion after surface ligand exchange; (3) Encapsulation of organic particles: PMMA particles with a particle size of 7 μm were dispersed in a toluene solution, and a dispersant BYK-156 with a mass fraction of 2% of PMMA particles was added to assist in dispersion. Then, a white light quantum dot dispersion after surface ligand exchange and a photoinitiator TPO were added. The mass ratio of the added white light quantum dots to the PMMA particles was 1:18, and the mass of the added photoinitiator was 2% of the total mass of the PMMA particles and the white light quantum dots. The reaction mixture was heated to 180 W / m 2 After UV irradiation and stirring at 600 rpm for 3 h, the mixture was dried to obtain organic particles coated with white light quantum dots. (4) preparing a coating liquid: firstly, ethyl acetate and butyl acetate are mixed in a volume ratio of 1:1 to prepare an organic mixed solvent, and then thermosetting acrylic glue, white light quantum dot-coated organic particles and additives are dissolved in the organic mixed solvent in proportion, and mixed evenly to prepare a coating liquid; the mass ratio of thermosetting acrylic glue to organic mixed solvent in the coating liquid is 1:2; (5) Coating: Use an OSP-20 wire rod to coat the coating liquid on the surface of the white reflective base film. The coating amount of the white light quantum dot-coated organic particles is 1.8 g / m2 After curing at 90° C. for 4 minutes, the coated reflective film containing white light quantum dot-coated organic particles was obtained.
[0045] Embodiment 3: A coated reflective film containing white light quantum dot-coated organic particles, comprising a white reflective base film (Ningbo Changyang Technology Co., Ltd., reflective film FDX150) with a thickness of 150 μm and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating include 6.8 parts of white light quantum dot-coated organic particles, 82 parts of thermosetting acrylic glue with a refractive index of 1.48 and 8 parts of a curing agent, 0.7 parts of an antistatic agent and 2.5 parts of a dispersant BYK-156.
[0046] The method for preparing the above-mentioned coating reflective film containing white light quantum dot-coated organic particles comprises the following steps: (1) Preparation of ZnCuGaInS / ZnS quantum dot dispersion: the method is the same as that in Example 1; (2) Quantum dot surface ligand exchange: dissolve pentaerythritol tetrathioglycolate in toluene to obtain a pentaerythritol tetrathioglycolate solution; mix the ZnCuGaInS / ZnS quantum dot dispersion and the pentaerythritol tetrathioglycolate solution at a mass ratio of ZnCuGaInS / ZnS quantum dots to pentaerythritol tetrathioglycolate of 1:40, stir and react at 1500 rpm for 4 h under nitrogen protection to obtain a white light quantum dot dispersion after surface ligand exchange; (3) Encapsulation of organic particles: PMMA particles with a particle size of 7 μm were dispersed in a toluene solution, and a dispersant BYK-156 with a mass fraction of 3% of PMMA particles was added to assist in dispersion. Then, a white light quantum dot dispersion after surface ligand exchange and a photoinitiator TPO were added. The mass ratio of the added white light quantum dots to the PMMA particles was 1:20, and the mass of the added photoinitiator was 2% of the total mass of the PMMA particles and the white light quantum dots. At 200 W / m 2 After UV irradiation and stirring at 400 rpm for 2 h, the mixture was dried to obtain organic particles coated with white light quantum dots; (4) preparing a coating liquid: firstly, ethyl acetate and butyl acetate are mixed in a volume ratio of 1:1 to prepare an organic mixed solvent, and then thermosetting acrylic glue, white light quantum dot-coated organic particles and additives are dissolved in the organic mixed solvent in proportion, and mixed evenly to prepare a coating liquid; the mass ratio of thermosetting acrylic glue to organic mixed solvent in the coating liquid is 1:2; (5) Coating: Use an OSP-20 wire rod to coat the coating liquid on the surface of the white reflective base film. The coating amount of the white light quantum dot-coated organic particles is 1.8 g / m 2 After curing at 120° C. for 2 minutes, the coated reflective film containing white light quantum dot-coated organic particles is obtained.
[0047] Embodiment 4: A coated reflective film containing white light quantum dot-coated organic particles, comprising a white reflective base film (Ningbo Changyang Technology Co., Ltd., reflective film FDX150) with a thickness of 150 μm and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating include 4 parts of white light quantum dot-coated organic particles, 85 parts of thermosetting acrylic glue with a refractive index of 1.48 and 8 parts of a curing agent, 0.7 parts of an antistatic agent and 2.3 parts of a dispersant BYK-156; the rest are the same as in Example 1.
[0048] Embodiment 5: A coated reflective film containing white light quantum dot-coated organic particles, comprising a white reflective base film (Ningbo Changyang Technology Co., Ltd., reflective film FDX150) with a thickness of 150 μm and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating include 8 parts of white light quantum dot-coated organic particles, 82 parts of thermosetting acrylic glue with a refractive index of 1.48 and 8 parts of a curing agent, 0.7 parts of an antistatic agent and 1.3 parts of a dispersant BYK-156; the rest are the same as in Example 1.
[0049] Embodiment 6: The difference between Example 6 and Example 1 is that in the white light quantum dot-encapsulated organic particles, the organic particles are PA particles with a particle size of 3 μm; the rest is the same as in Example 1.
[0050] Embodiment 7: The difference between Example 7 and Example 1 is that in the white light quantum dot-coated organic particles, the organic particles are PET particles with a particle size of 40 μm; the rest is the same as in Example 1.
[0051] Comparative Example 1: White reflective base film without coating (Ningbo Changyang Technology Co., Ltd., reflective film FDX150).
[0052] Comparative Example 2 (replaced with CdSe quantum dots): A coated reflective film containing quantum dot-coated organic particles, comprising a white reflective base film (Ningbo Changyang Technology Co., Ltd., reflective film FDX150) with a thickness of 150 μm and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating include 6.3 parts of quantum dot-coated organic particles, 82 parts of thermosetting acrylic glue with a refractive index of 1.48 and 8 parts of a curing agent, 0.7 parts of an antistatic agent and 3 parts of a dispersant BYK-156.
[0053] The method for preparing the above-mentioned coating reflective film containing quantum dot-coated organic particles comprises the following steps: (1) Preparation of CdSe quantum dot dispersion: CdSe powder (purchased from Nanocrystal Technology) was dispersed in toluene solvent to obtain a CdSe quantum dot dispersion with a mass fraction of 1%; (2) Quantum dot surface ligand exchange: dissolving pentaerythritol tetrathioglycolate in toluene to obtain a pentaerythritol tetrathioglycolate solution; mixing the CdSe quantum dot dispersion and the pentaerythritol tetrathioglycolate solution at a mass ratio of CdSe quantum dots to pentaerythritol tetrathioglycolate of 1:35, stirring and reacting at 1000 rpm for 4 h under nitrogen protection to obtain a quantum dot dispersion after surface ligand exchange; (3) Encapsulation of organic particles: PMMA particles with a particle size of 7 μm were dispersed in a toluene solution, and a dispersant BYK-156 with a mass fraction of 3% of PMMA particles was added to assist in dispersion. Then, a quantum dot dispersion after surface ligand exchange and a photoinitiator TPO were added. The mass ratio of the added CdSe quantum dots to the PMMA particles was 1:15, and the mass of the added photoinitiator was 2% of the total mass of the PMMA particles and the CdSe quantum dots. The reaction mixture was heated to 190 W / m 2 After UV irradiation and stirring at 500 rpm for 2 h, the mixture was dried to obtain quantum dot-coated organic particles; (4) preparing a coating liquid: firstly, ethyl acetate and butyl acetate are mixed in a volume ratio of 1:1 to prepare an organic mixed solvent, and then thermosetting acrylic glue, quantum dot-coated organic particles and additives are dissolved in the organic mixed solvent in proportion, and mixed evenly to prepare a coating liquid; the mass ratio of thermosetting acrylic glue to organic mixed solvent in the coating liquid is 1:2; (5) Coating: Use an OSP-20 wire rod to coat the coating liquid on the surface of the white reflective base film. The coating amount of the quantum dot-coated organic particles is 1.8 g / m 2 After curing at 100° C. for 3 minutes, the coated reflective film containing the quantum dots and organic particles was obtained.
[0054] Comparative Example 3 (white light quantum dots are not coated on the organic particles): A coated reflective film comprises a white reflective base film (Ningbo Changyang Technology Co., Ltd., reflective film FDX150) with a thickness of 150 μm and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating comprise 6.3 parts of PMMA particles with a particle size of 7 μm, 82 parts of thermosetting acrylic glue with a refractive index of 1.48 and 8 parts of a curing agent, 0.7 parts of an antistatic agent and 3 parts of a dispersant BYK-156.
[0055] The method for preparing the above-mentioned coated reflective film comprises the following steps: (1) Preparing a coating liquid: first, ethyl acetate and butyl acetate are mixed in a volume ratio of 1:1 to prepare an organic mixed solvent, and then thermosetting acrylic glue, PMMA particles and additives are dissolved in the organic mixed solvent in proportion, and mixed evenly to prepare a coating liquid; the mass ratio of thermosetting acrylic glue to the organic mixed solvent in the coating liquid is 1:2; (2) Coating: Use an OSP-20 wire rod to coat the coating liquid on the surface of the white reflective base film. The coating amount of PMMA particles is 1.8 g / m 2 ; After curing at 100° C. for 3 minutes, the coated reflective film is obtained.
[0056] Comparative Example 4 (without coating organic particles): A coated reflective film containing white light quantum dots, comprising a white reflective base film (Ningbo Changyang Technology Co., Ltd., reflective film FDX150) with a thickness of 150 μm and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating include 6.3 parts of ZnCuGaInS / ZnS quantum dots, 82 parts of thermosetting acrylic glue with a refractive index of 1.48 and 8 parts of a curing agent, 0.7 parts of an antistatic agent and 3 parts of a dispersant BYK-156.
[0057] The method for preparing the above-mentioned coating reflective film containing white light quantum dots comprises the following steps: (1) Preparation of ZnCuGaInS / ZnS quantum dots: centrifuging the ZnCuGaInS / ZnS dispersion prepared according to the method in Example 1, and drying the precipitate to obtain ZnCuGaInS / ZnS quantum dots; (2) Preparing a coating liquid: first, ethyl acetate and butyl acetate are mixed in a volume ratio of 1:1 to prepare an organic mixed solvent, and then thermosetting acrylic glue, ZnCuGaInS / ZnS quantum dots and additives are dissolved in the organic mixed solvent in proportion, and mixed evenly to prepare a coating liquid; the mass ratio of thermosetting acrylic glue to organic mixed solvent in the coating liquid is 1:2; (5) Coating: Use an OSP-20 wire rod to coat the coating liquid on the surface of the white reflective base film. The coating amount of ZnCuGaInS / ZnS quantum dots is 1.8 g / m 2 ; After curing at 100° C. for 3 minutes, the coated reflective film containing white light quantum dots is obtained.
[0058] Comparative Example 5 (no surface ligand exchange of quantum dots): The preparation method of the white light quantum dot-coated organic particles in Comparative Example 5 is: (1) Preparation of ZnCuGaInS / ZnS quantum dot dispersion: the method is the same as that in Example 1; (2) Encapsulation of organic particles: PMMA particles with a particle size of 7 μm were dispersed in a toluene solution, and a dispersant BYK-156 with a mass fraction of 3% of PMMA particles was added to assist in dispersion. Then, ZnCuGaInS / ZnS quantum dot dispersion and photoinitiator TPO were added. The mass ratio of the added ZnCuGaInS / ZnS quantum dots to the PMMA particles was 1:15, and the mass of the added photoinitiator was 2% of the total mass of the PMMA particles and the ZnCuGaInS / ZnS quantum dots. The reaction mixture was heated to 100 °C at 190 W / m 2 After UV irradiation and stirring at 500 rpm for 2 h, the mixture was dried to obtain organic particles coated with white light quantum dots; The rest are the same as in Example 1.
[0059] Comparative Example 6 (direct blending of white light quantum dots and organic particles): A coated reflective film containing white light quantum dots, comprising a white reflective base film (Ningbo Changyang Technology Co., Ltd., reflective film FDX150) with a thickness of 150 μm and a coating coated on the surface of the white reflective base film; in parts by weight, the raw materials in the coating include 0.4 parts of ZnCuGaInS / ZnS quantum dots, 5.9 parts of PMMA particles with a particle size of 7 μm, 82 parts of thermosetting acrylic glue with a refractive index of 1.48 and 8 parts of a curing agent, 0.7 parts of an antistatic agent and 3 parts of a dispersant.
[0060] The method for preparing the above-mentioned coating reflective film containing white light quantum dots comprises the following steps: (1) Preparation of ZnCuGaInS / ZnS quantum dots: centrifuging the ZnCuGaInS / ZnS dispersion prepared according to the method in Example 1, and drying the precipitate to obtain ZnCuGaInS / ZnS quantum dots; (2) Preparing a coating liquid: first, ethyl acetate and butyl acetate are mixed in a volume ratio of 1:1 to prepare an organic mixed solvent, and then thermosetting acrylic glue, ZnCuGaInS / ZnS quantum dots, PMMA particles and additives are dissolved in the organic mixed solvent in proportion, and mixed evenly to prepare a coating liquid; the mass volume ratio of thermosetting acrylic glue to organic mixed solvent in the coating liquid is 1:2; (5) Coating: Use an OSP-20 wire rod to coat the coating liquid on the surface of the white reflective base film. The coating amount of ZnCuGaInS / ZnS quantum dots is 1.8 g / m 2 ; After curing at 100° C. for 3 minutes, the coated reflective film containing white light quantum dots is obtained.
[0061] The properties of the coated reflective films prepared in the above examples and comparative examples were tested, and the results are shown in Table 1.
[0062] Among them, the test method of each performance is: Brightness uniformity test: Cut the coated reflective film into 10.1-inch size, assemble it into a 10.1-inch backlight module, and use a brightness meter (German model HS-1000) to perform a 13-point sampling test; uniformity indicates the uniformity of the brightness test value at each sampling point. The higher the uniformity, the better the uniformity.
[0063] Average brightness: It indicates the average value of the 13-point brightness test values sampled.
[0064] Relative brightness: Taking the brightness of the white reflective base film provided in Comparative Example 1 as 100%, the relative brightness of each embodiment and comparative example is calculated; the relative brightness is calculated as (average brightness of samples in each embodiment and comparative example / average brightness of samples in Comparative Example 1) × 100%.
[0065] Anti-adsorption test: Cut the coated reflective film into 10.1-inch size, assemble it into a 10.1-inch backlight module, light up the backlight module and put it into a vacuum adsorption inspection device. After vacuuming, observe whether there are bright spots on the backlight module. If there are more white spots, it means the anti-adsorption is poor, if there are fewer white spots, it means the anti-adsorption is average, and if there are no white spots, it means the anti-adsorption is excellent.
[0066] Table 1: Test results of reflective film coating performance
[0067] From the test results of anti-adsorption performance in Table 1, the large-size PET particles (Example 7) have better anti-adsorption performance than the small-size PA (Example 6) and PMMA particles, and the uncoated substrate (Comparative Example 1) has the worst anti-adsorption performance; in Comparative Example 4, only quantum dots are added without organic particles, and the anti-adsorption performance cannot be improved. However, with the increase of the particle size of the coated particles, the surface roughness of the coated reflective film increases, the uniformity decreases, and the uniformity of the light output is affected. From the brightness test results, as the proportion of organic coated particles coated with quantum dots increases, the brightness improvement effect becomes more significant. This is because after the proportion of quantum dots increases, the number of excited quantum dots in the coated reflective film increases, and the intensity of light reflected back to the upper part of the backlight module by the coated reflective film increases. In Comparative Example 3, quantum dots are not coated on the surface of organic particles, and the brightness decreases. It is worth noting that since white light quantum dots have light gain in the entire visible light band, the brightness improvement effect is better than that of CdSe quantum dots with single green light band fluorescence emission in Comparative Example 2. In Comparative Example 5, no ligand exchange is performed on the surface of the white light quantum dots, and the organic particles are directly coated. Since the original oleic acid and oleylamine ligands on the surface of the quantum dots cannot be chemically cross-linked with the surface of the organic coated particles, the brightness enhancement effect is not much different from the mechanical blending of Comparative Example 6. In addition, since the quantum dots cannot be dispersed as evenly as the organic coated particles, the light uniformity is also poor.
Claims
1. A coating reflective film containing white light quantum dots coated with organic particles, characterized in that: It includes a white reflective base film and a coating coated on the surface of the white reflective base film; the raw materials in the coating include white light quantum dot-coated organic particles, adhesives and additives; In the white light quantum dot-coated organic particles, the white light quantum dots are ZnCuGaInS / ZnS quantum dots after surface ligand exchange with molecules containing thiol functional groups, the organic particles are one or more of PMMA particles, PBMA particles, PET particles, and PA particles, and the particle size of the organic particles is 3~50μm.
2. The coating reflective film containing white light quantum dot-coated organic particles according to claim 1, characterized in that: In the white light quantum dots coated organic particles, the mass ratio of white light quantum dots to organic particles is 1:14~25.
3. The coating reflective film containing white light quantum dot-coated organic particles according to claim 1, characterized in that: The molecule containing a mercapto functional group is pentaerythritol tetrathioglycolate and / or γ-mercaptopropyltrimethoxysilane; During surface ligand exchange, the mass ratio of ZnCuGaInS / ZnS quantum dots and molecules containing thiol functional groups is 1:30~50.
4. The coating reflective film containing white light quantum dot-coated organic particles according to claim 1, characterized in that: In parts by weight, the raw materials in the coating include: 3 to 8 parts of white light quantum dot-coated organic particles, 75 to 85 parts of adhesive, and 8 to 12 parts of auxiliary agents; the refractive index of the adhesive is 1.43 to 1.
53.
5. The coating reflective film containing white light quantum dot-coated organic particles according to claim 4, characterized in that: The adhesive is one of thermosetting acrylic glue, polyurethane resin, epoxy resin, and polyvinyl acetal resin; the auxiliary agent is at least one of a dispersant, a curing agent, and an antistatic agent.
6. The coated reflective film containing white light quantum dot-coated organic particles according to claim 1 or 4, characterized in that: In the coating, the coating amount of the white light quantum dots coated organic particles is 1.5-2.5 g / m 2 .
7. The coating reflective film containing white light quantum dot-coated organic particles according to claim 1, characterized in that: The reflectivity of the white reflective base film is greater than 95%; the white reflective base film is one of a foamed polyethylene terephthalate base film, a polypropylene base film, and a polycarbonate base film.
8. A method for preparing a coating reflective film containing white light quantum dot-coated organic particles as claimed in any one of claims 1 to 7, characterized in that the steps include: (1) Preparation of ZnCuGaInS / ZnS quantum dot dispersion; (2) mixing the ZnCuGaInS / ZnS quantum dot dispersion and the molecular solution containing thiol functional groups, stirring and reacting to obtain a white light quantum dot dispersion after surface ligand exchange; (3) adding the white light quantum dot dispersion after surface ligand exchange to the dispersion of organic particles, and adding a photoinitiator, stirring and reacting under ultraviolet irradiation and drying to obtain white light quantum dot-coated organic particles; (4) Adding the raw materials in the coating into the organic solvent and mixing them evenly to form a coating liquid; (5) Apply the coating liquid on the surface of the white reflective base film and cure it.
9. The method for preparing a coating reflective film containing white light quantum dot-coated organic particles according to claim 8, characterized in that: The photoinitiator in step (3) is dimethylphenylphosphine or TPO; step (3) is at 180~200W / m 2 The mixture was irradiated with ultraviolet light and stirred at 400-600 rpm for 2-3 hours.
10. The method for preparing a coating reflective film containing white light quantum dot-coated organic particles according to claim 8, characterized in that: The organic solvent in the coating solution of step (4) is a mixed solvent of ethyl acetate and butyl acetate in a volume ratio of 1:0.5-2.
Citation Information
Patent Citations
Anti-adsorption coating type polyester film for reflection and preparation method thereof
CN105109166A
High-pressure-resistance and high-brightness coating type polyester reflecting film for mobile phone backlight module
CN114428416A
High-stability white light ZnCuGaInS / ZnS quantum dot and synthesis method thereof
CN117285930A
Quantum dot photoresist for manufacturing high-resolution pixels
CN118795731A
Quantum dot / nanosheet doped coating reflecting film and preparation method thereof
CN118994691A
Cited By
Preparation method of heat-insulating antibacterial steel plate
CN122060370A